2020
DOI: 10.21273/jashs04806-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vacuum Packaging on NAC Gene Expression in Fresh-cut Lotus Root

Abstract: NAC transcription factors have been characterized in numerous plants, and the NAC gene has been shown to be involved not only in plant growth and development, but also in plant responses to abiotic and biological stresses, such as drought, high salinity, low temperature, and anaerobic/hypoxic stress. Creating an environment of anaerobic/hypoxic stress has been shown to be one of the effective storage methods for delaying the browning of fresh-cut lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, NnANT and NnAP2 have been reported as potential negative regulators of lotus seed size and development ( Li et al, 2018b ). Moreover, the lotus NAC genes have been implicated in root browning under anaerobic stress and the formation of adventitious roots ( Cheng et al, 2019 ; Min et al, 2019 ). However, despite previous reports, comprehensive mapping of genome-wide NAC TF family, which could potentially improve our knowledge on the gene family function, distribution, and evolution in sacred lotus is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NnANT and NnAP2 have been reported as potential negative regulators of lotus seed size and development ( Li et al, 2018b ). Moreover, the lotus NAC genes have been implicated in root browning under anaerobic stress and the formation of adventitious roots ( Cheng et al, 2019 ; Min et al, 2019 ). However, despite previous reports, comprehensive mapping of genome-wide NAC TF family, which could potentially improve our knowledge on the gene family function, distribution, and evolution in sacred lotus is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Other research studies showed that phenylalanine ammonia lyase (PAL) and POD activities positively correlated with NAC expression. Thus, the low level expression of mdm-miR164b after H 2 S treatment increased the expression of NAC and might improve the antioxidant activity of fresh-cut apples, which was probably related to browning inhibition. However, the case difference in the delaying browning of fresh-cut lotus root by vacuum packaging, NnNAC1/4 was significantly suppressed, while NnNAC2 got induced . This discrepancy may result from the species-specific NAC member, as the function of NAC may be related to its types and plant species.…”
Section: Discussionmentioning
confidence: 95%
“…However, the case difference in the delaying browning of fresh-cut lotus root by vacuum packaging, NnNAC1/4 was significantly suppressed, while NnNAC2 got induced. 39 This discrepancy may result from the species-specific NAC member, as the function of NAC may be related to its types and plant species.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Various methods have been used to prolong the storage‐time of fresh‐cut lotus root. Oxalic acid treatment or vacuum packaging was able to suppress lotus browning by alleviating the activity of POD, PPO, and phenylalanine ammonia lyase (PAL) 6,7 . Enhancement of antioxidant enzyme activity has also suppressed the browning of fresh‐cut foods by reducing the levels of reactive oxygen species (ROS) 8 …”
Section: Introductionmentioning
confidence: 99%